2023
DOI: 10.1007/s00264-023-05946-z
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of drain versus no drain in total knee arthroplasty: a retrospective cohort study

Anas Albasha,
Loay A. Salman,
Ahmed Elramadi
et al.

Abstract: Purpose The use of suction drains in total knee arthroplasty (TKA) remains controversial. The aim of this study is to compare the outcomes of patients who received suction drains versus those who did not, focusing on blood loss, blood transfusion need, and length of hospital stay. Methods A retrospective observational cohort study was conducted at a tertiary hospital between January 1, 2015, and December 30, 2019, and included 262 patients who underwent un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 24 publications
0
2
1
Order By: Relevance
“…There is no consensus regarding the effect of CSD usage on LOS. While several studies have reported no signi cant difference, some large-scale studies have indicated that not using CSD can reduce LOS [22]. In our study, we observed a signi cant reduction in LOS in patients where CSD were not used, along with the combined use of local and systemic TA (P = 0.005).…”
Section: However Dressing Changes Were Not Observed In Non-csd Patientscontrasting
confidence: 43%
“…There is no consensus regarding the effect of CSD usage on LOS. While several studies have reported no signi cant difference, some large-scale studies have indicated that not using CSD can reduce LOS [22]. In our study, we observed a signi cant reduction in LOS in patients where CSD were not used, along with the combined use of local and systemic TA (P = 0.005).…”
Section: However Dressing Changes Were Not Observed In Non-csd Patientscontrasting
confidence: 43%
“…Previous literature has evaluated potential risks of drain use in lumbar spinal surgery and hip and knee arthroplasties, revealing a tendency for patients in which the drain was applied to receive more postoperative blood transfusions and to have a longer postoperative hospital stay [17][18][19][20][21]. [8,11].…”
Section: Discussionmentioning
confidence: 99%
“…In orthopedic procedures such as TKA, TXA is frequently utilized to minimize intraoperative and post-operative blood loss, thereby decreasing the need for blood transfusions and associated complications. Various studies confirmed the perioperative use of TXA provides a bloodless surgical field, reduces surgical drains, and thus prevents the need for allogeneic blood transfusion, and surgical drain [ 18 - 20 ].…”
Section: Introductionmentioning
confidence: 99%